Effect of Thermal Cycling on Abrasive Wear Response of Cu-1.9Be-0.25(Co+Ni) Alloy (2020)
Cu-Be alloys are considered high strength alloys when containing 0.2% to 2% of Be per weight, 0.2% to 2.7% of Co per weight, and up to 2.2% of Ni per weight, since they can present an elastic limit higher than 1380 MPa after aging (precipitation hardening), while, without heat treatment, they present an elastic limit between 205 MPa and 690 MPa [1]. Therefore, the complexity of the microstructure is a determining factor in the mechanical behavior of this type of alloys. In this work we analyzed the effect of microstructural variations obtained by cooling with water and with air from three different solubilization temperatures (750 °C, 800 °C and 850 °C) during 1 h, with and without aging, on the abrasive wear behavior of the Cu-1.9Be-0.25(Co+Ni) alloy. The chemical and microstructural characterization was performed by Dispersive Energy X-Ray Fluorescence (EDXRF) and Scanning Electron Microscopy (SEM-EDS), respectively. Abrasive wear behavior was evaluated under the guidelines of ASTM G65-16. Procedure E was used in this study, and the applied parameters were: force against the specimen (130 N), wheel revolutions (1000 rpm), linear abrasion (718 m) and test time (5 min). All tests were done in duplicate, showing a significant improvement in the abrasive wear behavior of the alloy, compared to the material in supply condition (T6). The lowest wear rates (<0.3 g/min) and volumetric loss (<200 mm3) were obtained with the specimens in solubilized condition with water cooling and without aging. The wear coefficients for the specimens with the highest resistance to abrasive wear are less than Ks=7x10-3. Keywords: abrasive wear; aging; copper-beryllium alloy; T6.